A fully human IgG1 antibody targeting MICA α1 domain inhibits interaction with NKG2D and activates immune effector functions against MICA-expressing cells - Campos, Ivo; González-Herrera, Fabiola; Guerra, Yuneisy; Garrido, María José; Fehring, Nicolás; Diaz, Carla; Matthies, Douglas J.; González, Mauricio; Tello, Samantha; Tempio, Fabián; Vásquez, Gonzalo; Rodríguez-Siza, Jose; et al. (Frontiers in Immunology, 2026)
BackgroundMICA is a stress-induced ligand for the activating receptor NKG2D and plays a central role in immune recognition and elimination of tumor cells. Tumor-derived soluble MICA (sMICA) and its allelic diversity impair immune responses by disrupting NKG2D function and promoting immune evasion, highlighting the need for antibody-based strategies targeting the MICA/NKG2D axis.MethodsWe generated a fully human IgG1 monoclonal antibody targeting the α1 domain of MICA using phage display and rational epitope design focused on a conserved, low-polymorphic region. We characterized its binding specificity and affinity for MICA, competition with NKG2D, and its ability to trigger immune effector functions, including antibody-dependent cell cytotoxicity (ADCC), antibody-dependent cell phagocytosis (ADCP) and activation of the classical complement pathway.ResultsThe antibody displayed high affinity for recombinant MICA (app Kd ≈ 20 nM) and effectively competed with NKG2D (Ki ≈ 15 nM). It recognized multiple MICA alleles expressed in human gastric and leukemia cell lines, confirming broad allelic coverage. Functional assays showed that the antibody mediated strong CDC, ADCC by NK cells and promoted ADCP of MICA-expressing cells.ConclusionBy combining high-affinity recognition of broad MICA alleles and robust activation of immune effector functions, this fully human anti-MICA α1 antibody offers a novel strategy to modulate the MICA/NKG2D axis and activate Fc-mediated immune effector functions against MICA-expressing tumor cells. Its dual mechanism of action supports its development as a standalone or combinatorial agent with immune checkpoint inhibitors in MICA-expressing tumors.